Interaction of Various Ecological Factors on Benthic Macroinvertebrate and River Health. Issue 1 (1st November 2022) - Aweng, E R; Aisyah, S O S; Salam, M A; Liyana, A A; Mior, I B
Abstract : River health is an aspect that goes beyond river cleanliness. This is because a clean river does not necessarily have life in it but a healthy river do. The ecological component is a factor that affects aquatic life which at the same time describes the level of river health. To answer this question, a study to identify the relationship between ecological factors and aquatic life with river health was conducted. This study was conducted in Sungai Mengkibol, Sungai Madek and Sungai Dengar in Johor. There were a total of five sampling sites, three for impact stations and two as reference stations, including one highland station. Total of seven elements namely ecological indices, physico-chemical water quality, river riparian, canopy cover, large woody debris (LWD), river discharge and substrate composition were measured and analyzed. Surber net measuring 500 micron mesh size combined with a rectangular quadrate of 30 cm x 30 cm (0.09 m 2 ) were used to sample the benthic macro-invertebrate. Chi-square test was performed to determine the association level between one variable with another, meanwhile Pearson's R value was analyzed to determine the correlation level either it is strong or weak. The results show that, all river ecological components have a significant correlation to the benthic macroinvertebrate ecological indices, however the association was varies. Based on the chi-square test, Pearson's value, p and Pearson's R value, the interplay (interaction) of various ecological factors on aquatic life forms and river health was produced with various p-value<0.05 and R-value is more than 0.5. It can be suggested that the ecological indices for benthic macroinvertebrates can be used as an indicator to assess river health.